The perspectives, barriers, and willingness of Utah dentists to engage in human papillomavirus (HPV) vaccine practices. Issue 2 (1st February 2020) - Harris, Katherine L.; Tay, D.; Kaiser, D.; Praag, A.; Rutkoski, H.; Dixon, B. L.; Pinzon, L. M.; Winkler, J. R.; Kepka, D.
ABSTRACT: Including dental health providers in human papillomavirus (HPV) vaccination could reduce rising rates in HPV-associated oropharyngeal cancer (HPV-OPC). This study assessed Utah dentists' perspectives on providing HPV vaccination education and services in the dental setting. A cross-sectional, 70-item self-administered survey was conducted among a convenience sample of N = 203 practicing Utah dentists. Statistical analyses included Chi Square tests of independence, scaled scores and Cronbach's alpha coefficients. Majority of Utah dentists surveyed perceived that discussing the link between HPV and OPC and recommending the HPV vaccine is within their scope of practice, but not administration of the HPV vaccine. Dentists with >10 minutes of patient education per week were less likely to be concerned about the cultural, social norms or religious ideology of discussing HPV with their patients ( p = .024). Rural dentists were more concerned about the safety and liability of the HPV vaccine ( p = .011). Good internal consistency was observed survey items regarding barriers and willing to engage in HPV vaccination practices. Dental providers were interested in HPV training and patient education brochures as strategies, but less interested in administering the HPV vaccine. Dental associations support dentists' engagement in HPV education and HPV-OPC prevention. This is the first study in Utah to examine dentists' perspectives on HPV vaccination. Findings have implications for program planning, intervention development, and future research.